Specificity and exclusiveness of human capital and corporate control in Chinese entrepreneurial firms - Lei Wang; Yunbi An; Jun Yang (South African Journal of Business Management, 2018)
Background: Entrepreneur was the key factor of venture capital-backed star-ups, and control rights serve as an important incentive to attract entrepreneurs' human capital investment.Objective: In this article, we investigate the ways in which the specificity and exclusiveness of entrepreneurs' human capital impact the allocation of residual control right (RCR) and specific control right (SCR) in entrepreneurial firms, based on the comprehensive effect of various control right benefits.Methods: Using panel data for a mixed regression model, we test theoretical hypotheses with survey data collected from entrepreneurial firms in various industries in China.Results: We find that when the venture capitalist's (VC) strategic benefits are less than the entrepreneur's private benefits, the VC's RCR is negatively related to the specificity of the entrepreneur's human capital and is positively related to the exclusiveness of the entrepreneur's human capital. The VC's SCR is positively related to the specificity and is negatively related to exclusiveness. When the VC's strategic benefits are greater than the entrepreneur's private benefits, the VC's RCR is positively related to the specificity of the entrepreneur's human capital and is negatively related to the exclusiveness. The VC's SCR is positively related to both the specificity and exclusiveness.Conclusion: The impacts of specificity and exclusiveness of human capital are more significant for high-tech companies than for traditional companies. It is necessary for different types of VC-backed firms to implement classified governance over the control rights.
Keywords: 650